Problem-Based Learning versus STAD Leaning Model for Improving Students' Argumentation Skills in Thermochemistry - Tyas, Frida Kristining; Dasna, I Wayan; Wijaya, Anugerah Ricky; Setyowati, Istri (FKIP Universitas Lampung, 2023)
This study investigates whether the use of the Problem-Based Learning (PBL) model and Cooperative learning STAD can improve argumentation skills in the thermochemistry chapter. The research sample is 72 grade 11 high school students. The research design was quasi-experimental with a pretest-posttest control group design. The results of the study: (1) there was no difference in initial ability between the PBL and CL STAD classes with a significance value of > 0.00; (2) there are differences in argumentation skills between PBL and CL STAD classes with a significance value <0.00; (3) the PBL model N-Gain test was 60.50% in the